Isolation, identification and characterization of microorganisms involved in rubber odour production / Nornanysya Feroze Khan - Feroze Khan, Nornanysya (2013)
The presence of obnoxious odour is due to microbial reactions that could lead to harmful effects to the environment. This study was aimed to investigate the correlation between microorganisms and rubber odour production. There were 23 isolates possibly producing the odour isolated from various sampling points of rubber plantation at Felda Kg. Awah, Temerloh Pahang and were identified using VITEK®2 System analysis. From the observation, Kocuria kristinae was found to be the common species in this study since it was isolated at all sampling sites. Furthermore, 15 isolates were selected for analysis of rubber odour production using solid-phase microextraction (SPME) and Gas Chromatography Mass Spectrometry (GC-MS). The analysis showed that, the volatile components detected comprised of hydrocarbon and low molecular weight compounds such as volatile fatty acids, amino and sulphurcontaining compound, esters and alcohol. There were 18 odorous compounds detected in this study mainly comprised of 5H-Naphto[2,3-c] carbazole,5-methyl-; 7HDibenzo[b,g] carbazole,7-methyl and camphene. However, in order to suppress the growth of microorganism that lead to the production of odorous compounds, three different antimicrobial agents (Sodium hypochlorite, Chloroxylenol and Formaldehyde) as well as HISKA® were used. The treated rubber was subjected to SPME/GCMS analysis to check for the absence, of volatile components. The analysis showed that 0.5% (w/v) and 1.0% (w/v) formaldehyde followed by 1.0% (w/v) and 3.0% (w/v) sodium hypochlorite were able to inhibit the microbial growth and at the same time eliminate the unpleasant odour. The cure characteristics and physical properties of the vulcanized rubber base on ACS 1 mix formulation were evaluated. The treated rubber showed a better quality, hence enhanced the physical properties such as tensile strength, hardness and resilience when compared to SMR L.